Economic Losses from Flaring Gases in Rumaila Oil Field - Abbas, Hamza Abdulkhudhur; Sultan, Hussein Sadiq (Basrah Journal for Engineering Sciences, 2024)
Flaring systems used in oil production systems have a significant impact on both the economy and the environment as they discharge large quantities of burned gases of elevated temperature to the atmosphere that have the potential to be used in some applications. This study aims to investigate the economic losses incurred due to the combustion of gases not utilized in the Rumaila oil field in Basrah, the southern region of Iraq. Additionally, the potential to use flare gases for power generation and water desalination was studied. The mathematical models established by the U.S. Environmental Protection Agency (EPA) were utilized in this study to estimate and calculate the expected losses and used MatLab Ver. R22 to get result. The result leads to expected annular economic losses to reach $ 347,735,700. Also, the flare gases can be used to produce electric power of 1175 MW per year, it can be used for producing desalinating water of 115,911,900 m 3 for thermal desalination and 173,867,850 m 3 for membrane desalination.